Calling in Context: Relational Fracture and Divine Initiative in Genesis - Henry Darmawan (Voice, 2026)
Divine calling is often framed within coherent and purpose-driven models that emphasize clarity and fulfillment. Yet, such approaches tend to overlook the disruptive relational contexts in which calling is discerned. This study examines the role of relational fracture in the formation of calling, focusing on sibling narratives in Genesis. Using a biblical-theological approach with a narrative-critical orientation, the study analyzes the accounts of Cain and Abel, Jacob and Esau, and Joseph and his brothers. The findings demonstrate that relational fracture does not function as a formative mechanism of calling, but as a revelatory and destabilizing condition that exposes how individuals respond to divine initiative. The same condition of fracture produces divergent outcomes—distortion in Cain, transformation in Jacob, and providential formation in Joseph—indicating that suffering does not possess inherent formative power. Instead, the outcome is determined by the dynamic interplay between divine initiative and human response. This study contributes to a more precise theological framework by redefining relational fracture as a revelatory condition rather than a formative process, offering a nuanced understanding of calling that is grounded in biblical narrative and responsive to the complexity of human experience.